Context-Sensitivity and Individual Differences in the Derivation of Scalar Implicature - Yang, Xiao; Minai, Utako; Fiorentino, Robert (Frontiers in Psychology, 2018)
The derivation of scalar implicatures for the quantifier some has been widely studied to investigate the computation of pragmatically-enriched meanings. For example, the sentence “I found some books” carries the semantic interpretation that at least one book was found, but its interpretation is often enriched to include the implicature that not all the books were found. The implicature is argued to be more likely to arise when it is relevant for addressing a question under discussion (QUD) in the context, e.g., when “I found some books” is uttered in response to “Did you find all the books?” as opposed to “Did you find any books?”. However, most experimental studies have not examined the influence of context on some, instead testing some sentences in isolation. Moreover, no study to our knowledge has examined individual differences in the ability to utilize context in interpreting some, whereas individual variation in deriving implicatures for some sentences in isolation is widely attested, with alternative proposals attributing this variation to individual differences in cognitive resources (e.g., working memory) or personality-based pragmatic abilities (e.g., as assessed by the Autism Spectrum Quotient). The current study examined how context influences the interpretation of some in a story-sentence matching task, where participants rated some statements (“I cut some steaks”) uttered by one character, in response to another character’s question (QUD) that established the implicature as relevant (“Did you cut all the steaks?”) or irrelevant (“Did you cut any steaks?”). We also examined to what extent individuals’ sensitivity to QUD is modulated by individual differences via a battery of measures assessing cognitive resources, personality-based pragmatic abilities, and language abilities (which have been argued to modulate comprehension in other domains). Our results demonstrate that QUD affects the interpretation of some, and reveal that individual differences in sensitivity to QUD are modulated by both cognitive resources and personality-based pragmatic abilities. While previous studies have argued alternatively for cognitive resources or personality-based pragmatic abilities as important for deriving implicatures for some in isolation, we argue that arriving at a context-sensitive interpretation for some depends on both cognitive and personality-based properties of the individual.